Analisis Potensi Penggunaan Hall Dalam Industri Mice Di SMK Trisakti Ngawi - Sugiman Sugiman; Husen Danung Sulaksana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Over time, it is not only the tourism industry that has the potential to support the MICE industry, one of which is educational institutions such as vocational schools and equivalent. However, there are three factors that need to be considered, namely Hall management, supporting facilities, and work programs, so that good MICE services are obtained and are able to gain profits for the institution. Trisakti Ngawi Vocational School (SMK Trisakti Ngawi) has professional Hall management, adequate Hall support facilities and a suitable work program to carry out MICE (Meeting, Incentive, Conference and Exhibition) activities